Evaluating the validity and economy of the English language teaching textbook evaluation checklist - Mukundan, Jayakaran; Hossein, Vahid Nimehchisalem (IDOSI Publications, 2012)
This paper presents a part of an on-going project that aims at developing an instrument to evaluate English language teaching textbooks, called the English Language Teaching (ELT) Textbook Evaluation Checklist. The present study sought to evaluate the validity, reliability and economy of the developed checklist. It also aimed to find out to what extent the users of the checklist were satisfied with it. Two ELT experts used the checklist to evaluate the same textbook. The inter-rater reliability results showed acceptable reliability coefficients (r=.88). The checklist was tested for the correlation of its results with those of a well-established instrument [1] and a high correlation (r=.77) was observed. The instrument also proved to be economical. On average, it took the two experts almost three times shorter as compared to the time they spent using the Skierso checklist. The evaluators turned out to be highly satisfied with the checklist and highly agreed on its usefulness. Despite the promising findings of this study, further research is needed to shed light on the possible problems of the checklist and improve its validity, reliability and practicality.